The Relationship between Inflation and Interest Rate: Panel Regression and Causality Analyses on OECD Countries - Sugözü, İbrahim Halil; Yaşar, Sema (Maliye Bakanlığı, 2020)
The relationship between the interest rate and inflation is one of the most discussed issues in macroeconomic studies, especially within the scope of the Fisher and Neo-Fisher effect. In this study, panel causality analyzes are applied by using a quarterly dataset between 2001 and 2019 in 32 OECD countries, and the form and power of this relationship are tried to be explained by a regression analysis. With the existence of cross-section dependence, the Hausman test, autocorrelation and heteroscedasticity tests are performed, and the stationarity of the variables are analyzed by the CADF test. Finally, variables are found to affect each other positively and strongly according to the Driscoll-Kraay test. In the last two panel causality analyses, it is shown that there is bilateral causality between changes in inflation and the interest rate.
Keywords: Inflation; Interest; Neo-Fisher Effect; Panel Causality Analysis